2018
DOI: 10.1093/schbul/sby018.826
|View full text |Cite
|
Sign up to set email alerts
|

S39. Gpr139 an Ophan GPCR Affecting Negative Domains of Schizophrenia

Abstract: BackgroundIndividuals with schizophrenia fail to appropriately use negative feedback to guide learning. These learning deficits are thought to arise from abnormalities in midbrain dopamine activity. The habenula is a well conserved paired structure that sits in the midline, adjacent to the third ventricle, and dorsal and posterior to the thalamus. Classic studies have shown that it is part of the reward pathway and functions with dopamine neurons in the ventral tegmental area (VTA) to mediate reward related si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Interestingly, in light of the DRD2/GPR139 mRNAs co-expression found in the mesolimbic pathway (projects from VTA to nucleus accumbens and Tu) (Ikemoto, 2010), a recent preclinical study using the selective GPR139 agonist JNJ-63533054 showed that GPR139 receptor activation reverses key addiction-like behaviors in dependent animals (Kononoff et al, 2018). Another GPR139 agonist 4-oxo-3,4-dihydro-1,2,3-benzotriazine has been reported to improve social withdrawal in a preclinical model of the negative symptom of schizophrenia (Atienza et al, 2018), involving the mesocortical pathway (initiate from VTA but instead project to the prefrontal cortex) (Ekhtiari and Paulus, 2016). A recent study reported that the GPR139 agonist TC-O 9311 (structurally identical to compound 1a used in this study) protected primary mesencephalic dopamine neurons against 1-methyl-4-phenylpyridinium (MPP+)-mediated degeneration, indicating a potential role of GPR139 in neuroprotection and Parkinson’s disease (Bayer Andersen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in light of the DRD2/GPR139 mRNAs co-expression found in the mesolimbic pathway (projects from VTA to nucleus accumbens and Tu) (Ikemoto, 2010), a recent preclinical study using the selective GPR139 agonist JNJ-63533054 showed that GPR139 receptor activation reverses key addiction-like behaviors in dependent animals (Kononoff et al, 2018). Another GPR139 agonist 4-oxo-3,4-dihydro-1,2,3-benzotriazine has been reported to improve social withdrawal in a preclinical model of the negative symptom of schizophrenia (Atienza et al, 2018), involving the mesocortical pathway (initiate from VTA but instead project to the prefrontal cortex) (Ekhtiari and Paulus, 2016). A recent study reported that the GPR139 agonist TC-O 9311 (structurally identical to compound 1a used in this study) protected primary mesencephalic dopamine neurons against 1-methyl-4-phenylpyridinium (MPP+)-mediated degeneration, indicating a potential role of GPR139 in neuroprotection and Parkinson’s disease (Bayer Andersen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of several selective agonists, the physiological function of GPR139 remains elusive. Its potential role in addiction (Kononoff et al, 2018), Parkinson’s disease (Bayer Andersen et al, 2016), locomotor activity (Liu et al, 2015), and schizophrenia (Atienza et al, 2018) has been suggested. L-Trp and L-Phe are the precursors for serotonin and dopamine biosynthesis, respectively, which are neurotransmitters implicated in mood regulation (Toker et al, 2010; Anjema et al, 2011; ten Hoedt et al, 2011; Jenkins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…GPR139 knockout mice show impaired episodic-like memory, working memory, and motivation, while a GPR139 agonist reverses impaired cognitive flexibility in mouse models of CIAS. 233 A phase II proof-of-concept clinical trial was completed in September 2019 assessing the procognitive and motivational efficacy of the GPR139 agonist TAK-041 as an add-on treatment for schizophrenia patients with CIAS. While results are yet to be posted, TAK-041 remains an active program.…”
Section: Working Memorymentioning
confidence: 99%
“…Bayer Andersen et al have recently reported that the GPR139 agonist TC‐O 9311 protected primary mesencephalic dopamine neurons against 1‐methyl‐4‐phenylpyridinium (MPP+)‐mediated degeneration, indicating a potential role of GPR139 in neuroprotection and Parkinson's disease . Another GPR139 agonist, 4‐oxo‐3,4‐dihydro‐1,2,3‐benzotriazine, has been reported to improve social withdrawal …”
Section: Introductionmentioning
confidence: 99%
“…11 Another GPR139 agonist, 4-oxo-3,4-dihydro-1,2,3-benzotriazine, has been reported to improve social withdrawal. 12 From a structural perspective, Kaushik and Sahi reported a three dimensional structure prediction and molecular dynamics simulation of GPR139 model. Further structure-based virtual screening was applied and several active site residues of GPR139, including Tyr32, Glu105, Glu108, and Tyr192, have been identified as potential ligand binding sites for inhibition of protein dimerization and receptor activity.…”
Section: Introductionmentioning
confidence: 99%